Complements or Substitutes? Preferential and Multilateral Trade Liberalization at the Sectoral Level - Mitsuyo Ando; Antoni Estevadeordal; Christian Volpe Martincus (Asian Development Bank (ADB), 2009)
This paper explores the relationship between preferential and multilateral trade liberalization at the sectoral level using a unique dataset that includes data on most favored nation (MFN) and bilateral preferential tariffs at the 4-digit ISIC level for 11 Latin American countries over the period 1985–2005. We find evidence of heterogeneity across sectors. While in some industries, complementary effects between both kinds of trade liberalization are observed, in others no significant links are detected and—in a few cases—even substitutability seems to prevail. Variation across sectors appears to be systematically related to both import demand elasticities and countries' sectoral comparative advantages.
hdl:11540/1832
Keywords: C20; F13; F14; 330; Trade liberalization; regionalism; Latin America